2014
DOI: 10.1167/iovs.13-13703
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacologic Alternatives to Riboflavin Photochemical Corneal Cross-Linking: A Comparison Study of Cell Toxicity Thresholds

Abstract: There are significant differences in cell toxicity among potential topical cross-linking compounds. The balance between cross-linking of tissue and cell toxicity should be borne in mind as compounds and strategies to improve mechanical tissue properties through therapeutic tissue cross-linking continue to develop.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 58 publications
1
33
0
Order By: Relevance
“…Formaldehyde-releasing agent cell cytotoxicity assays were performed as we have previously described. 33 Briefly, healthy human skin fibroblasts (HSFs) from American Type Culture Collection (ATCC, Manassas, VA, USA) were cultured in dermal cell basal media (ATCC) using a serum-free fibroblast growth kit provided by the company (ascorbic acid, EGF/TGF-b1, glutamine, hydrocortisone, insulin, and fibroblast growth supplements). Cells were grown in 5% CO 2 and 95% ambient air at 378C until confluent.…”
Section: Far Cytotoxicity Thresholdmentioning
confidence: 99%
“…Formaldehyde-releasing agent cell cytotoxicity assays were performed as we have previously described. 33 Briefly, healthy human skin fibroblasts (HSFs) from American Type Culture Collection (ATCC, Manassas, VA, USA) were cultured in dermal cell basal media (ATCC) using a serum-free fibroblast growth kit provided by the company (ascorbic acid, EGF/TGF-b1, glutamine, hydrocortisone, insulin, and fibroblast growth supplements). Cells were grown in 5% CO 2 and 95% ambient air at 378C until confluent.…”
Section: Far Cytotoxicity Thresholdmentioning
confidence: 99%
“…The majority of this research focuses on new antiinflammatory molecules or innovative technologies to induce transepithelial CXL. 50,51 It is possible that in the future, the researchers will find a topical medication that could directly influence the progression of keratoconus and other corneal ectasias.…”
Section: Nonsurgical Treatmentmentioning
confidence: 99%
“…This result is in accordance with previously published data on the toxicity of this crosslinking agent. 29 It is worth mentioning that this toxic effect was clearly concentration-dependent. Zhong et al reported the use of vapors of GA to efficiently crosslink polysaccharide structures without toxic effect associated.…”
Section: Discussionmentioning
confidence: 94%